Building MSME Competitiveness in the Digital Era: The Role of Human Capital Development and Digital Leadership through Entrepreneurial Orientation - Pristanto Ria Irawan; Ganjar Garibaldi; Joelianti Dwi Supraptiningsih (Fundamental and Applied Management Journal, 2026)
The rapid advancement of digital transformation has significantly altered the competitive landscape of Micro, Small, and Medium Enterprises (MSMEs), particularly in the food and beverage sector. To remain competitive, MSMEs must strengthen their internal capabilities through human capital development, effective digital leadership, and entrepreneurial orientation. This study investigates the effects of Human Capital Development and Digital Leadership on MSME Competitiveness, with Entrepreneurial Orientation serving as a mediating variable. A quantitative explanatory research design was employed, and data were collected from 250 food and beverage MSMEs operating in North Jakarta, Indonesia. Respondents were selected using purposive sampling based on predefined business criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that Human Capital Development and Digital Leadership positively and significantly influence Entrepreneurial Orientation. Furthermore, both variables have significant direct effects on MSME Competitiveness, with Human Capital Development emerging as the strongest predictor. Entrepreneurial Orientation also exerts a positive influence on competitiveness and significantly mediates the relationships between Human Capital Development and Competitiveness, as well as between Digital Leadership and Competitiveness. The structural model demonstrates strong explanatory and predictive power, with R² values of 0.773 for Entrepreneurial Orientation and 0.864 for SME Competitiveness. This study contributes to the literature by integrating Human Capital Development, Digital Leadership, Entrepreneurial Orientation, and Competitiveness into a unified framework grounded in the Resource-Based View and Dynamic Capabilities perspectives. The findings provide practical insights for MSME owners, managers, and policymakers regarding strategies for strengthening competitiveness and sustaining business growth in the era of digital transformation.